Progress in degradation of volatile organic compounds based on low‐temperature plasma technology. Issue 4 (17th January 2020) - Chang, Zhengshi; Wang, Cong; Zhang, Guanjun
Abstract: On the basis of plasma technology, the progress of the volatile organic compounds' (VOCs') degradation by low‐temperature plasma alone is discussed first, including reactor types, influencing factors of plasma degradation of VOCs and the reaction mechanism between plasma and VOCs. Then, the research status of three VOC degradation technologies (catalysis, adsorption, and biotechnology) and their synergistic degradation of VOCs with plasma are reviewed, including the effect of catalyst position on VOC degradation, the interaction mechanism between plasma and catalyst; the factors affecting the adsorption of VOCs by carbon‐based adsorbents and zeolite, the degradation of VOCs by plasma‐assisted adsorbent; the features of different biological systems, the influencing factors of VOC degradation by the biotrickling system, and the degradation of VOCs by plasma‐assisted biotreatment. Finally, the prospects of developments in high‐tech based on plasma are discussed. Abstract : On the basis of plasma technology, this article introduces plasma‐related degradation technologies of volatile organic compounds (VOCs), including the influencing factors and reaction mechanism of VOC degradation by single plasma; the interaction mechanism between plasma and different catalyst systems; the factors affecting the adsorption of VOCs and its removal by plasma‐assisted adsorbent, and the synergistic degradation of VOCs with plasma and biological treatment technology